2021
DOI: 10.17533/udea.iee.v39n3e10
|View full text |Cite
|
Sign up to set email alerts
|

Poor glycemic control and associated factors in diabetic people attending a reference outpatient clinic in Mato Grosso, Brazil

Abstract: Objective. To identify the proportion of poor of glycemic control and associated factors among people with type 2 diabetes attending a regional reference outpatient clinic in Mato Grosso (Brazil). Methods. This is a cross-sectional quantitative study based on data from medical records of 338 people with type 2 diabetes who attend a state reference outpatient clinic in Mato Grosso (Brazil). Information on glycemic control, sociodemographic factors, lifestyle and clinical conditions was collected. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…This systematic review included 12 articles that met the eligible criteria (Table 1) [16][17][18][19][20][21][22][23][24][25][26][27]. The included articles were published either in 2021 [16][17][18][19][20][21][22] or in 2020 [23][24][25][26][27]. No articles were published in 2022.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This systematic review included 12 articles that met the eligible criteria (Table 1) [16][17][18][19][20][21][22][23][24][25][26][27]. The included articles were published either in 2021 [16][17][18][19][20][21][22] or in 2020 [23][24][25][26][27]. No articles were published in 2022.…”
Section: Resultsmentioning
confidence: 99%
“…There were 10 cross-sectional studies [16,[18][19][20][21][22][23][24][25]27], whereas the remaining two studies were either retrospective observational [17] or retrospective [26]. Among the cross-sectional studies, there were seven studies that reported a cross-sectional design only [18][19][20][22][23]25,27], whereas the remaining three studies reported that the studies were prospective cross-sectional [16], descriptive-analytical cross-sectional [21], and descriptive cross-sectional [24]. The overall prevalence of poor glycemic control was 45.2%…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations